Bruce Andrews and Charles Bernstein's L=A=N=G=U=A=G=E : the complete facsimile - Hofer, Matthew; Golston, Michael; Andrews, Bruce, 1948-; Bernstein, Charles, 1950- (Albuquerque : University of New Mexico Press, 2020)
Bruce Andrews and Charles Bernstein's L=A=N=G=U=A=G=E: The Complete Facsimile makes available in print all twelve of the newsletter's original issues along with three supplementary issues.
Online resource; title from digital title page (viewed on June 02, 2020).
eBooks on EBSCOhost
Keywords: Poetry, Modern -- 20th century -- Periodicals; Literature, Modern -- 20th century -- Periodicals; Literature, Modern -- 20th century -- History and criticism -- Periodicals; Poésie -- 20e siècle -- Périodiques.; Littérature -- 20e siècle -- Périodiques.; Littérature -- 20e siècle -- Histoire et critique -- Périodiques.; Literature, Modern; Poetry, Modern; 1900-1999; Periodical; facsimiles (reproductions); periodicals; Criticism, interpretation, etc; Facsimiles; Periodicals; Facsimiles; Periodicals; Fac-similés.; Périodiques.